Variables del modelo BSM en el mercado colombiano (2012)
The option pricing model performed by Black-Scholes-Merton has become the most important and studied worldwide, which is why it has become the benchmark and the most used when making a quote and subsequent closure of the currency market. On the other hand, is known to the operators that model variables are quite rigid, as they are called that only would occur in an environment in which there were no price gaps presented by the illiquidity of currencies during certain periods 24 hours a day or that may be determined in advance as volatility or interest rates in the evolution of a currency against another. In this paper I intend to show that in markets like Colombia are situations in which evidence of the importance of not underestimating any variable.